Pekanbaru City District Regional Development Model: (Case Study of Binawidya District Expansion) - Aguswan; Widia Astuti; Trio Saputra (Kemudi, 2023)
This study aims to find a model for the development of the subdistrict area by strengthening the functions of the sub-district work field in improving services to the community. The research approach is descriptive qualitative, explaining and revealing the existence of the implementation of public services. Data collection techniques through action and development through observation, interviews, documentation and then analyzed and drawn conclusions. the results of the study, that a structured and systematic regional development model can facilitate the sub-district government in actualizing policies, programs of development activities and empowerment of the community.